Quantifying survey expectations: What's wrong with the probability approach? - Jörg Breitung; Maik Schmeling (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2011)
We study a matched sample of individual stock market forecasts consisting of both qualitative and quantitative forecasts. This allows us to test for the quality of forecast quantification methods by comparing quantified qualitative forecasts with actual quantitative forecasts. Focusing mainly on the widely used quantification framework advocated by Carlson and Parkin (1975), the so-called probability approach, we find that quantified expectations derived from the probability approach display a surprisingly weak correlation with reported quantitative stock return forecasts. We trace the reason for this low correlation to the importance of asymmetric and time-varying thresholds, whereas individual heterogeneity across forecasters seems to play a minor role. Hence, our results suggest that qualitative survey data may not be a very useful device to obtain quantitative forecasts and we suggest ways to remedy this problem when designing qualitative surveys.
Keywords: C53; D84; G17; 330; Quantification; Stock Market Expectations; Probability Approach; Heterogeneity